Foreign Policy, Islam and Democracy in Indonesia - Dewi Fortuna Anwar (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2010)
The relations between Islam and Democracy in Indonesia and their implications forthe countrys foreign policy have attracted considerable attention in recent years. Inthe early years of his frst presidential term, Susilo Bambang Yudhono introduced the concept of Indonesias international identity, that is, as a country in which Islam, democracy and modernity go hand in hand. In the post-9/ international context, in which perceptions of Islam are largely negative, Indonesias special attributes as the largest Muslim-majority country and the worlds third largest democracy have special values. The international community, especially Western countries, has looked to Indonesia to provide an alternative face of Islam in the midst of rising religious extremism and terrorism. Indonesia, however, still faces many challenges in realising its aspirations to be a bridge between the Islamic world and the West, and as an alternative model within the Islamic world. Frequent acts of religious intolerance have marred Indonesias claim as a moderate Islamic force while Indonesia has generally been perceived to lie in the periphery of the Islamic world.